Morphological characteristics of antennal microstructure and its ecological significance in xanthopimpla pedator (hymenoptera: ichneumonidae: pimplinae): insights into cocoon-concealed host detection - Gathalkar, Ganesh B.; Sharma, V. Pooja; Barsagade, Deepak D. (Microscopy and Microanalysis, 2026)
Xanthopimpla pedator (Fabricius) (Hymenoptera: Ichneumonidae: Pimplinae) is a specialist solitary pupal endoparasitoid of the tropical Tasar silkworm, Antheraea mylitta (Drury) (Lepidoptera: Saturniidae), causing significant ecological and economic losses each year. Female oviposits into cocoon-concealed pupae of A. mylitta, where the developing larva consumes the host, ultimately killing it. During host searching, females rely on their antennae as the principal sensory organs to detect and evaluate host suitability, although sensory structures on the ovipositor may also contribute to oviposition decisions. Scanning electron microscopy (SEM) revealed nine distinct microstructure/sensilla types: trichodea, basiconica, chaetica, placodea, grooved peg sensilla, campaniformia, microtrichia, B & ouml;hm's bristles, and glandular pores, including their respective subtypes. Additional microstructures, such as apical pegs, cuticular pores, and cuticular folds, were also observed. Sensilla trichodea were most abundant, followed by placodea, chaetica, and basiconica. Apical pegs at the antennal apex in both sexes are hypothesized to function in vibrational sounding during antennal tapping. Minimal sexual dimorphism in antennal sensilla was observed, limited to antennal length and flagellomere counts. These antennal features, including chemosensory and mechanosensory sensilla, are likely essential for host detection, discrimination, and oviposition, providing insights that could inform the development of semiochemical-based pest management tactics.
Keywords: antennal sensilla; endoparasitoid; host detection; scanning electron microscopy; tasar silkworm; ultrastructure